Premarital Screening and Genetic Counseling program: Knowledge, attitude, and satisfaction of attendees of governmental outpatient clinics in Jeddah - Nahla Khamis Ibrahim; Jamel Bashawri; Hussein Al Bar; Jawaher Al Ahmadi; Adnan Al Bar; Mahdi Qadi; Waleed Milaat; Hashim Feda (Elsevier, 2013)
Summary: Premarital care (PMC) is a worldwide activity that aims to diagnose and treat unrecognized disorders and reduce the transmission of diseases to couples and children. Objectives: To assess the knowledge and attitude of individuals attending governmental outpatient clinics regarding the Premarital Screening and Genetic Counseling (PMSGC) programs, to identify predictors of high knowledge scores and to determine the satisfaction and recommendations of clients of the program. Methods: A cross-sectional study was conducted from January to April 2009. Individuals who attended three governmental hospital outpatient clinics on the day of the interview and agreed to participate in the study were recruited. The three hospitals were the two hospitals in Jeddah that offer the PMSGC programs and the King Abdulaziz University Hospital. Ethical considerations were followed and data were collected through an interview questionnaire that had been constructed for the study. The questionnaire asked for personal and socio-demographic data and for responses, on a 5-point Likert scale, to 30 knowledge items and 14 attitude statements. Individuals who participated in the PMSGC program were asked questions regarding the services and activities of the program to ascertain their satisfaction with the program and their recommendations for program improvement. The statistical analysis was performed using SPSS version 16 (SPSS Inc., Chicago, IL). Results: The sample included 655 participants, of whom 38.8% completed the PMSGC program. The participants' knowledge about the program was generally low. Education was the first predictor of a high knowledge score; individuals having ≥ university degree obtained a higher score (aOR = 2.73; 95% CI: 1.77-4.20). The second predictor was the nationality of the participants, with Saudis gaining a higher score (aOR = 2.04; 95% CI: 1.002-4.16). The third predictor was monthly income. Regarding attitudes, the vast majority of participants (96.0%) strongly agreed on the importance of the program. Concerning the satisfaction levels of those who benefited from the program, 80.0% gave an excellent or very good score for program confidentiality, whereas lower scores were given for counseling. Counseling before the tests was conducted for only 11.7% of the study participants. The majority of participants recommended adding testing for other genetic diseases and STDs as well as additional topics for counseling. Conclusion: Knowledge in the general population about the PMSGC program was low. Implementation of school and university educational campaigns is important. Improved counseling and adding new topics for counseling on genetic, chronic, and psychiatric problems; building healthy families; reproduction and fertility are recommended. Keywords: Knowledge, Attitude, Satisfaction, Premarital, Outpatient attendees